If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 * 16 + -14 * 14 + -1g = 6 Multiply 16 * 16 256 + -14 * 14 + -1g = 6 Multiply -14 * 14 256 + -196 + -1g = 6 Combine like terms: 256 + -196 = 60 60 + -1g = 6 Solving 60 + -1g = 6 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -1g = 6 + -60 Combine like terms: 60 + -60 = 0 0 + -1g = 6 + -60 -1g = 6 + -60 Combine like terms: 6 + -60 = -54 -1g = -54 Divide each side by '-1'. g = 54 Simplifying g = 54
| 10(-3)-(-6)+9= | | 0.002x-0.005=0.012+0.04 | | 6200=x^2-10x+4200 | | 3(a-1)+4= | | 4x+15=31 | | x^2+x=380 | | 2x-13=21 | | 9x+x-2x=0 | | y-1x=5 | | Z+18=9z-7 | | 184-3x=33x+16 | | x^2+35x-36=0 | | 100+5y=3(2y-4) | | -4(y+7)=-9y-8 | | 8x-7w+5x+9y+4y+5w= | | 3x-23=16 | | 2(x+3)=3(x+2)-x | | -8u-42=-5(u+6) | | .86=16t^2 | | 5[2x+3(2x-1)]=2(5x+3) | | 34.3=4.9*n | | 86=16t^2 | | 34.3=4.9 | | 8(w+9)=-7w-48 | | 2x+8=-2(x+6) | | 2(t-3)+6t=4(2t+5)-9 | | 8x=192 | | -33-5x=8x+18 | | 1-(6+x)=3-4(x-1) | | a^2=a^3 | | 8x-4+5x+8=90 | | 2x+13=-95-10 |